Language-specific aspects of reading acquisition: the case of Russian - Rubinov, Evgenia (fi=Turun yliopisto|en=University of Turku|, 2015)
We have investigated Russian children’s reading acquisition during an intermediate period in their development: after literacy onset, but before they have acquired well-developed decoding skills. The results of our study suggest that Russian first graders rely primarily on phonemes and syllables as reading grain-size units. Phonemic awareness seems to have reached the metalinguistic level more rapidly than syllabic awareness after the onset of reading instruction, the reversal which is typical for the initial stages of formal reading instruction creating external demand for phonemic awareness. Another reason might be the inherent instability of syllabic boundaries in Russian. We have shown that body-coda is a more natural representation of subsyllabic structure in Russian than onset-rime. We also found that Russian children displayed variability of syllable onset and offset decisions which can be attributed to the lack of congruence between syllabic and morphemic word division in Russian. We suggest that fuzziness of syllable boundary decisions is a sign of the transitional nature of this stage in the reading development and it indicates progress towards an awareness of morphologically determined closed syllables. Our study also showed that orthographic complexity exerts an influence on reading in Russian from the very start of reading acquisition. Besides, we found that Russian first graders experience fluency difficulties in reading orthographically simple words and nonwords of two and more syllables. The transition from monosyllabic to bisyllabic lexical items constitutes a certain threshold, for which the syllabic structure seemed to be of no difference. When we compared the outcomes of the Russian children with the ones produced by speakers of other languages, we discovered that in the tasks which could be performed with the help of alphabetic recoding Russian children’s accuracy was comparable to that of children learning to read in relatively shallow orthographies. In tasks where this approach works only partially, Russian children demonstrated accuracy results similar to those in deeper orthographies. This pattern of moderate results in accuracy and excellent performance in terms of reaction times is an indication that children apply phonological recoding as their dominant strategy to various reading tasks and are only beginning to develop suitable multiple strategies in dealing with orthographically complex material. The development of these strategies is not completed during Grade 1 and the shift towards diversification of strategies apparently continues in Grade 2.

Lukemaan oppimisen erityispiirteet venäjän kielessä Venäjänkielisten lasten lukemaan oppimista tutkittiin sen välivaiheessa eli ensi askelien jälkeen mutta ennen kuin tekninen lukeminen oli ehtinyt kehittyä varmaksi ja sujuvaksi. Tulokset antavat tukea näkemykselle, että venäläiset ensiluokkalaiset tukeutuvat ensisijaisesti äänteisiin ja tavuihin lukemisen perusyksikköinä. Lukemisen opetuksen alettua äännetietoisuus saavuttaa metakielellisen tason nopeammin kuin tavutietoisuus, koska muodollinen opetus luo painetta äännetietoisuuden hyväksi. Toinen syy saattaa olla venäjän kielelle ominainen tavurajojen epävakaus.Venäjänkielisten ensiluokkalaisten välillä on tuntuvia eroja siinä, miten hyvin he pystyvät havaitsemaan tavun alkamisen ja päättymisen kohdat. Taustalla vaikuttavat tavuihin ja morfeemeihin perustuvien sanarajojen ero. Lukijan edistyminen morfeemien määräämien suljettujen tavujen havaitsemiseen näkyy ohimenevänä epävarmuutena tavurajojen havaitsemisessa. Tulokset osoittivat myös, että oikeinkirjoituskäytänteiden monimutkaisuus vaikuttaa lukemaan oppimiseen alusta lähtien. Lisäksi havaittiin, että venäjänkieliset ensiluokkalaiset kohtaavat vaikeuksia yrittäessään lukea sujuvasti kahden tai useamman tavun mittaisia sanoja tai epäsanoja, vaikka näiden rakenne olisi yksinkertainenkin. Siirtyminen yksitavuisista kaksitavuisiin sanoihin näyttää täten muodostavan kynnyksen, joka on tavurakenteesta riippumaton. Kun venäjänkielisten ensiluokkalaisten tuloksia verrataan muunkielisten lasten tuloksiin, oli heidän suoriutumisensa samalla tasolla kuin äänteenmukaisesti kirjoitettavaa kieltä puhuvien lasten lukeminen sellaisissa sanoissa, joissa kirjain – äänne käännös on selkeä. Toisaalta venäjänkielisten lasten lukeminen muistutti epäsäännöllisesti kirjoitettavien kielten alkavien lukijoiden suoritusta sellaisissa sanoissa, joissa kirjain – äänne vastaavuus on epätäydellinen. Toisin sanoen, tuloksissa näkyi sanan lukemisen keskinkertainen tarkkuus yhdistyneenä nopeuteen. Myös tämä havainto tukee tulkintaa, että alkavat lukijat luottavat ensisijaisesti äänteenmukaiseen strategiaan ja ovat vasta aloittamassa joustavien strategioiden käytön, mitä tarvitaan kirjoitusasultaan monimutkaisissa sanoissa. Tämä siirtymävaihe jatkuu vielä toisella luokalla.